Management von chronischem Schmerz mit retardiertem Tilidin: Lebensqualität und Bedeutung der Komedikation für den Tilidinmetabolismus - Wolfert, Christina Lisa; Meid, Andreas; Burhenne, Jürgen; Blank, Antje; Mikus, Gerd (Der Schmerz, 2017)
Background and objectivesThe synthetic opioid tilidine is often used in chronic pain treatment. However, the activation via metabolism in patients with concomitant medication and reduced liver or kidney function is not thoroughly investigated. We therefore studied pain treatment efficacy, health-related quality of live and the metabolism of tilidine in patients with chronic pain.Methods and materialsIn all, 48 patients, who were on a stable dose of oral prolonged release tilidine for at least 7 days, were included in this observational multicenter study. Liver and kidney function were assessed in routine blood samples, concentrations of tilidine, nortilidine and bisnortilidine were determined using a validated LC/MS/MS method. Comedication was registered and patients experience with regard to quality of life, pain, gastrointestinal symptoms and adverse events was assessed in standardised questionnaires.ResultsOn average a daily dose of 180 mg tilidine was taken. Dose normalized plasma concentrations of the active metabolite nortilidine ranged between 1.6 ng/ml and 76.5 ng/ml (mean 29.2 ± 25.1 ng/ml). Ratios between tilidine and nortilidine were on average 0.28 (median = 0.13, standard deviation = 0.67). Patients were on 1 to 14 different concomitant medications. About 66% of the patients had sufficient pain treatment. Almost no opioid-induced constipation was observed. Only few patients had decreased kidney or liver function which did not result in elevated nortilidine concentrations.ConclusionPain treatment using tilidine resulted in variable nortilidine concentrations which are obviously not strongly influenced by comedication or reduced liver or kidney function. Only a few side effects were observed with almost no opioid-induced constipation.